Effect of pro- and metabiotic Lactobacillus delbrueckii D5 strain on myocardial resistance to ischemia – reperfusion injury in the rat model of systemic inflammatory response - Yu. Yu. Borshchev; S. M. Minasean; N. Yu. Semenova; I. Yu. Burovenko; O. V. Borshcheva; E. Yu. Gritsenko; V. A. Sheptitsky; A. N. Suvorov; M. M. Galagudza (Бюллетень сибирской медицины, 2024)
Aim. To study the effect of lyophilized L. delbrueckii D5, as well as its inactivated culture, during intragastric administration on myocardial resistance to ischemia – reperfusion injury (IRI), markers of inflammation, and intestinal epithelial permeability. Materials and methods. The experiments were performed on male Wistar rats with a model of systemic inflammatory response syndrome (SIRS). Myocardial IRI was reproduced on an isolated Langendorff heart. Results. A significant increase in the levels of tumor necrosis factor (TNF)α, interleukin (IL)-1β, IL-6, and lactoferrin in SIRS was revealed. The introduction of both inactivated and lyophilized culture of L. delbrueckii D5 resulted in normalization of these changes. Normalization of the increased blood level of lipopolysaccharide in SIRS was also noted with the introduction of both inactivated and lyophilized L. delbrueckii D5. However, the inactivated culture had no effect on the myocardial infarct size, which was increased in the SIRS group compared to the controls, whereas the introduction of the lyophilized strain led to a significant decrease in this parameter. Conclusion. The inactivated culture of Lactobacillus delbrueckii D5 has a pronounced anti-inflammatory effect, but does not impact myocardial resistance to IRI, unlike the lyophilized strain, which requires further research.